'Made in China 2025' and China's cross-border strategic M&As in OECD countries. Issue 2 (2nd April 2020) - Lin, Yue
ABSTRACT: This article focuses on the highly debated 'Made in China 2025' program and its effects on Chinese M&As in OECD countries. Difference-in-differences as well as difference-in-difference-in-differences statistical techniques are employed to calculate to what extent 'Made in China 2025' has shaped both sector composition and location choice of Chinese M&As in the OECD, and to estimate effects and limits of national policies on cross-border M&As. Based on statistical results we can argue that 'Made in China 2025' has induced a new 'troika' model, of which the significance is moderated by firm-specific characteristics, such as ownership structure, and the firm's home country embeddedness level. However, while we observe location diversification of Chinese M&As in the OECD at the aggregate level, hosting countries' FDI screening mechanisms have no significant impact on containing China's M&As that target more sensitive sectors.